Research landscape and frontiers of non-alcoholic steatohepatitis-associated hepatocellular carcinoma: a bibliometric and visual analysis - Gao, Bowen; Chen, Zhiheng; Shi, Meijie; Mo, Yousheng; Xiao, Huanming; Xie, Yubao; Lin, Ming; Chi, Xiaoling (Frontiers in Pharmacology, 2023)
Background: Due to the widespread prevalence of caloric excess and sedentary behavior on a global scale, there is a growing body of epidemiological evidence indicating that non-alcoholic steatohepatitis (NASH) has rapidly become a leading aetiology underlying of hepatocellular carcinoma (HCC). In light of the escalating incidence of NASH-associated HCC (NASH-HCC), it is imperative to mitigate the impending burden. While there has been an increase in global awareness regarding this issue, it has yet to be examined from a bibliometric standpoint. Therefore, this study seeks to provide a comprehensive bibliometric analysis to characterize the evolution of this field. Method: The present study utilized the Web of Science Core Collection (WoSCC) to identify publications pertaining to NASH-HCC over the past 2 decades. Employing Vosviewer 1.6.19, CiteSpace 6.2.R2, and the Analysis Platform of Bibliometrics, the study conducted an analysis of various dimensions including the quantity of publications, countries, institutions, journals, authors, co-references, keywords, and trend topics in this field. Results: A comprehensive analysis of 3,679 publications pertaining to NASH-HCC, published between 1 January 2002 and 1 April 2023, was conducted. The field in question experienced a rapid increase in publications, with the United States serving as the central hub. Collaboration between institutions was more extensive than that between countries. Notably, HEPATOLOGY (n = 30,168) emerged as the most impactful journal, and Zobair M. Younossi (n = 10,025) as the most frequently cited author in co-citations. The most commonly cited references were KLEINER DE, 2005, HEPATOLOGY (n = 630), followed by YOUNOSSI ZM, 2016, HEPATOLOGY (n = 493). The author keywords were categorized into three distinct clusters, namely, Cluster 1 (Mechanism), Cluster 2 (Factors), and Cluster 3 (Diagnosis). Analysis of high-frequency co-occurring keywords and topical trends revealed emphasis on molecular mechanisms in current research. “macrophages” and “tumor microenvironment” were active research hotspots at present in this field. Conclusion: A bibliometric analysis was performed for the first time on publications pertaining to non-alcoholic steatohepatitis-hepatocellular carcinoma, uncovering co-research networks, developmental trends, and current research hotspots. The emerging frontiers of this field focused on the macrophages and tumor microenvironment, especially the tumor-associated macrophages, offering a fresh perspective for future research directions.